2005
DOI: 10.1073/pnas.0409891102
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of a deep animal divergence by the pattern of intron conservation

Abstract: The relationship between three biologically important groups, arthropods, nematodes, and deuterostomes, remains unresolved. It is unknown whether arthropods are more closely related to nematodes (consistent with the ''ecdysozoa'' hypothesis) or to deuterostomes (consistent with ''coelomata''). We present a method in which we use the pattern of spliceosomal intron conservation to develop a series of inequalities that characterize each possible relationship. We find that only the ecdysozoa grouping satisfies the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 31 publications
(45 reference statements)
4
26
0
Order By: Relevance
“…phosphatase in Fig. 4) suggest that ancient protein domains were composed of many exons (or contained many introns), which has also been proposed in other studies [22,36,38]. The current study suggest a minimum exon length around 4 nucleotides, similar to modern minimum reported exon lengths (see [39] for exon sizes).…”
Section: Discussionsupporting
confidence: 90%
“…phosphatase in Fig. 4) suggest that ancient protein domains were composed of many exons (or contained many introns), which has also been proposed in other studies [22,36,38]. The current study suggest a minimum exon length around 4 nucleotides, similar to modern minimum reported exon lengths (see [39] for exon sizes).…”
Section: Discussionsupporting
confidence: 90%
“…Intron positions have been used successfully to delineate the deep phylogenetic relationships (Rogozin et al 2005). Roy and Gilbert used pattern of intron conservation to resolve the deep phylogenetic relationship between the arthropods, nematodes, and deuterostomes (Roy and Gilbert 2005), suggesting that intron positions could be considered as informative phylogenetic marker. Following which, others have used introns as an informative marker to resolve phylogenetic relationships (Krauss et al 2008;Rokas and Holland 2000;Zheng et al 2007).…”
Section: Feasibility Of Use Of Introns As Informatic Phylogenetic Marmentioning
confidence: 99%
“…We note in passing that there is some ongoing debate [20][21][22][23] as to whether the phylogenetic tree of Fig. 2 is correct, namely, whether Ecdysozoa are monophyletic.…”
Section: Intron Evolution In Eukaryotesmentioning
confidence: 99%
“…Philippe et al [22] argue that they are, and that support for other hypotheses are due to long branch attraction phenomena. Roy and Gilbert [21] also argue for an ecdysozoan clade, based on the intron data set of [4]. We consider only one phylogenetic tree, and leave further analysis to a more complete version of this abstract.…”
Section: Intron Evolution In Eukaryotesmentioning
confidence: 99%